Alcohol use and mental health during COVID-19 lockdown: A cross-sectional study in a sample of UK adults. (1st February 2021) - Jacob, Louis; Smith, Lee; Armstrong, Nicola C.; Yakkundi, Anita; Barnett, Yvonne; Butler, Laurie; McDermott, Daragh T.; Koyanagi, Ai; Shin, Jae Il; Meyer, Jacob; Firth, Joseph; Remes, Olivia; et al.
Highlights: More than one in six UK adults increased their alcohol consumption during lockdown. Increased alcohol consumption was associated with poor overall mental health. These findings highlight the importance of planning targeted support. Abstract: Background: The aim was to examine the correlates of increased alcohol consumption during the COVID-19 pandemic-related restrictions that were implemented in a sample of UK adults. Methods: This paper presents analyses of data from a cross-sectional study. Adults aged 18 years and over, residing in the UK and self-isolating from others outside their own household were eligible to participate. Participants reported increase or no increase in their level of alcohol consumption from before to during lockdown, as well as symptoms of anxiety, depression and mental wellbeing. Socio-demographic characteristics were compared between adults with and without reported increased alcohol consumption. The associations between reported increased alcohol consumption and mental health outcomes were investigated using logistic and linear regression analyses. Results: 691 adults (61.1 % women; 48.8 % aged 35−64 years) were included in the analysis. Of these, 17 % reported increased alcohol consumption after lockdown. A higher proportion of 18−34-year olds reported increased alcohol consumption compared to older groups. The prevalence of poor overall mental health was significantly higher in individuals with increased alcohol consumption (vs. no increase) (45.4 % versus 32.7 %; p-value = 0.01). There was a significant association between increased alcohol consumption and poor overall mental health (OR = 1.64; 95 % CI = 1.01, 2.66), depressive symptoms (unstandardized beta = 2.93; 95 % CI = 0.91, 4.95) and mental wellbeing (unstandardized beta=-1.38; 95 % CI=-2.38, -0.39). Conclusions: More than one in six UK adults increased their alcohol consumption during lockdown and a higher proportion of these were younger adults. Increased alcohol consumption was independently associated with poor overall mental health, increased depressive symptoms and lower mental wellbeing. These findings highlight the importance of planning targeted support as we emerge from lockdown and plan for potential second and subsequent waves.